(3eNJUQ GdePcQ hGdeDfKs - (3GdeanqVd Hf SdeI Hf YGUe, CHh WGdH,J (B290 (3g` s ((3CHh GdaQL eMeO Hf ZHQGgje GdCUHgGfi s)
(3ChdgG (B:s
(3GYde Cf GdaQb Hjf GdePcQ hGdeDfK KdGK YdGeGJ Jchf ai GdeDfK efgG GdgGA fMh adGf hadGfI s
(3BNQgG (B:s
(3bGdhG (B: (3VHYGf , hGdCQfH CfKi , hGdGSe ddPcQ hGdCfKi , aEPG CQGgG GdPcQ bGdhG (B: (3NRf , aGageg aEfg WQja Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B120 - (3U(B125s
(3HChdgG bQGAI fGSN GdcJGHs
(3Ydi GdWjH GHf Ydi jQhjg Yf eMeO Hf ESeGYjd Hf HdHds
(3Yf CHj WGdH GdeaVd Hf SdeI cJHgG HjOg GdWjH Hf Ydi ai TgQ QLH SfI (B352(3gs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B314s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B22 s
Keywords: (3GddZIs